“Menguak Eksploitasi Seksual terhadap Perempuan dan Anak” Pendekatan Kritik Ideologi terhadap Teks Kejadian 19:30-38 - Novembry Patty; Febby Nancy Patty (Views : Jurnal Teologi dan Biblika, 2026)
This research focuses on the exploitation of women and children by their own parents. This research focuses on the hermeneutics of biblical texts that tend to discriminate against women and children. The qualitative research method uses a literature study approach with an ideological criticism approach, which is divided into three stages, namely, dominant ideology, counter-ideology, and alternative ideology as a solution to the inequality of justice in the text. Next, the author conducted a literature study as a data collection method to process the research material. The author uses information sources obtained from the literature in the form of reference books, the Bible, journals, and dictionaries. This is an attempt to rediscover the textual messages contained in the Bible, which are connected to the present day to see and raise the experiences, struggles, and struggles of women and children towards liberation from male-centered biblical texts. From the results of the interpretation, several dominant ideologies were found, namely patriarchy, extreme survivalism, the normalization of domestic sexual violence, scapegoating against women, and ethnic exclusivism. From this, the author proposes an alternative ideology as a middle way to address the problems found. The alternatives offered are the ideology of restoring human dignity, the ideology of trauma awareness, the ideology of relational responsibility, and the ideology of human solidarity. Ultimately, all of these alternative ideologies culminate in the formation of a transformative theology of life, one that reads texts not simply as documents of the past but as sources of critical reflection to confront the realities of violence and injustice in the present.